Uzbekistan and international law - Dilmurodov Dilmurod Dilshodjon o‘g‘li; Raxmonaliyev Nurislom Dilshodjon o‘g‘li (International Journal on Orange Technologies, 2020)
International law is an authoritative legal system that is recognized and followed by states around the world. The preamble to the Constitution of the Republic of Uzbekistan also strengthens the recognition of the primacy of international law and its universally recognized principles. This means that the Republic of Uzbekistan firmly declares that the principles and rules of international law take precedence over the national law of the country. Therefore, a thorough study and knowledge of international law is the primary task of lawyers and specialists in all fields of social sciences. The emergence of our independent state in the international arena and its full participation in international relations requires a thorough study of the relevant international legal institutions and criteria. In recent years, the role of international law as a means of fair regulation of international relations has been growing worldwide